2010
DOI: 10.1179/acb.2010.069
|View full text |Cite
|
Sign up to set email alerts
|

PREVALENCE AND GENETIC HETEROGENEITY OFBORRELIA BURGDORFERISENSU LATO INIXODESTICKS IN BELGIUM

Abstract: Borrelia burgdorferi sensu lato is a genetically diverse group of spirochetes that includes the agent of Lyme borreliosis in which genospecies tend to be associated with specific clinical features. The aim of the study was to determine the prevalence and genetic diversity of Borrelia burgdorferi sensu lato in 524 ticks collected in woods of a western province of Belgium. Presence of spirochetes in ticks was determined by phase contrast microscopy. The mean infection rate of ticks was 12.0%. Variability was obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 7 publications
4
14
0
Order By: Relevance
“…3, 29). Together with other recent studies in Belgium and Luxembourg [33,35] our results show that besides B. valaisiana, B. spielmanii and B. lusitaniae are also present in Ixodes in the Benelux region. B. garinii, B. afzelii and B. burgdorferi s.s. are well known to be pathogenic for humans, but the pathogenic significance of the other species is still unclear [36,37].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…3, 29). Together with other recent studies in Belgium and Luxembourg [33,35] our results show that besides B. valaisiana, B. spielmanii and B. lusitaniae are also present in Ixodes in the Benelux region. B. garinii, B. afzelii and B. burgdorferi s.s. are well known to be pathogenic for humans, but the pathogenic significance of the other species is still unclear [36,37].…”
Section: Discussionsupporting
confidence: 89%
“…was within the range of infection rates (2.3-22%) in ticks collected from dogs in other European countries [3,16,29-31]. Similar infection rates were also reported in questing I. ricinus in Belgium (12-23%) [32,33]. Within the B. burgdorferi sensu lato group, B. afzelii and B. garinii are the most common species in The Netherlands, Belgium and northern France, while B. burgdorferi s.s. is less common in this region [34].…”
Section: Discussionsupporting
confidence: 83%
“…In Belgium, LD is due to at least five species: Borrelia afzelii , B. garinii , B. burgdorderi sensu stricto (ss) , B. spielmanii , and B. valaisiana (29, 30). A prior study indicated the most prevalent genospecies in Belgian ticks was B. garinii (53% of infected ticks), followed by B. burgdoreferi ss (38%) and B. afzelii (9%) (31).…”
Section: Discussionmentioning
confidence: 99%
“…For some sites additional details were provided by authors, however, the methodology is already described in published articles and summarised in the Additional file 1. This includes (1) Collection BAYER, 579 sites [13], (2) Collection RLVBD, 51 sites [14], (3) Collection UGENT FOREST, 33 sites [15,16], (4) Collection ARSIA, 17 sites [17], (5) Collection UCLIREC, 5 sites [18], and (6) Collection UA1, 16 sites [7,19-22]. Collection GREY DATA includes tick field observations from the website of NATAGORA and NATUURPUNT (http://www.observations.be, http://www.waarnemingen.be) by registered users involved with nature related activities from 1980 until February 2012.…”
Section: Methodsmentioning
confidence: 99%